Impact of FAAH genetic variation on fronto-amygdala function during emotional processing - Gärtner, Anne; Witt, Stephanie (European archives of psychiatry and clinical neuroscience, 2019)
Recent translational studies identified a common endocannabinoid polymorphism, FAAH C385A, in the gene for the fatty acid amide hydrolase (FAAH). This polymorphism alters endocannabinoid anandamide levels, which are known to be involved in the fronto-amygdala circuitry implicated in mood regulation and anxiety-like behaviors. While it has been shown that the variant that selectively enhances fronto-amygdala connectivity at rest is associated with decreased anxiety-like behaviors, no study so far has investigated whether this finding of FAAH-related differential plasticity extends to task-related differential functional expression and regulation during negative emotional processing. Using an imaging genetics approach, this study aimed to replicate and extend prior findings by examining functional activity and task-related connectivity in fronto-amygdala regions during emotion reactivity and emotional down-regulation of negative affect. Therefore, 48 healthy young adults underwent a functional MRI resting state measurement, completed an emotion regulation paradigm and provided self-reports on anxiety and use of emotion regulation strategies. In line with previous studies, preliminary evidence suggests that A-allele carriers demonstrate stronger fronto-amygdala connectivity during rest. In addition, exploratory whole-brain analyses indicate differential functional activity of A-allele carriers during emotion reactivity and emotion regulation. There were no associations with anxiety-related self-reports and use of emotional regulation strategies. Further research using larger samples and polygenic approaches is indicated to clarify the precise role and its underlying mechanisms in emotion processing.
First online: 05 October 2018
Gesehen am 04.07.2019